2009
DOI: 10.1007/s11605-009-0849-z
|View full text |Cite
|
Sign up to set email alerts
|

Predictive and Prognostic Value of CA 19-9 in Resected Pancreatic Adenocarcinoma

Abstract: Our findings do not support a cutoff value for CA 19-9 that is associated with margin or lymph node involvement. Preoperative CA 19-9 < or = 120 U/ml is, however, associated with increased overall and recurrence-free survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 86 publications
(58 citation statements)
references
References 16 publications
1
55
0
2
Order By: Relevance
“…Preoperative CA 19.9 levels below certain threshold were associated with increased overall and recurrence-free survival (29). The evidence that the chemovirotherapy treatment reduced CA 19.9 levels by 95% was a clear confirmation of the effective reduction in the tumor mass.…”
Section: Discussionmentioning
confidence: 87%
“…Preoperative CA 19.9 levels below certain threshold were associated with increased overall and recurrence-free survival (29). The evidence that the chemovirotherapy treatment reduced CA 19.9 levels by 95% was a clear confirmation of the effective reduction in the tumor mass.…”
Section: Discussionmentioning
confidence: 87%
“…Its clinical usefulness in the diagnosis [21], the assessment of resectability [14], monitoring the progression [11] and determining the prognosis of pancreatic cancer has been reported [7-13]. Ferrone et al [20] reported that the preoperative level of CA19-9 was not an independent prognostic factor in patients with resectable pancreatic adenocarcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…To date, several studies have reported that the preoperative carbohydrate antigen 19-9 (CA19-9) level, which is a tumor-associated antigen that requires the expression of a sialylated Lewis blood group antigen for expression, is a useful marker for predicting prognosis after resection [5-13]. However, the cutoff value of CA19-9 used to predict prognosis varied among these reports.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, most FDA-approved cancer biomarkers are glycoproteins or carbohydrate antigens (Adamczyk, Tharmalingam, & Rudd, 2012;Barton et al, 2009;Ludwig & Weinstein, 2005). Many of these existing glycoprotein biomarkers could potentially be improved for specificity and sensitivity by incorporating a tumor-specific glycoform.…”
Section: Opportunities and Challengesmentioning
confidence: 99%